Analysis of diagnostic error cases among Japanese residents using diagnosis error evaluation and research taxonomy. (4th January 2021) - Harada, Taku; Miyagami, Taiju; Watari, Takashi; Hiyoshi, Tetsuya; Kunitomo, Kotaro; Tsuji, Takahiro; Shimizu, Taro
Abstract: The process of diagnostic errors among Japanese residents has not been previously studied. This descriptive study was conducted in June 2019 on junior residents at a single‐center educational hospital in Japan. Diagnosis Error Evaluation and Research taxonomy was used to measure the process of diagnostic error in the most memorable error cases. High frequency of diagnostic errors resulted from inaccurate/misinterpretation of history, failure/delay in eliciting physical examination findings, inaccurate/misinterpretation of physical examination, failure in weighting of physical examination, and failure/delay in considering the diagnosis. Residents made diagnostic errors mainly during history taking, physical examination, and assessment. Abstract : According to the analysis of diagnostic error cases among Japanese residents using Diagnosis Error Evaluation and Research taxonomy, diagnostic errors are mainly caused during medical history collection, physical examination, and clinician evaluation.